1994
DOI: 10.1101/gad.8.11.1300
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis or retinoblastoma: alternative fates of photoreceptors expressing the HPV-16 E7 gene in the presence or absence of p53.

Abstract: A transgenic mouse model for retinoblastoma was produced previously by directing SV40 T antigen expression to retinal photoreceptor cells using the promoter of the interstitial retinol-binding protein (IRBP) gene. This gene becomes active prior to the terminal differentiation of photoreceptors. Because T antigen-transforming activity is attributable, at least in part, to the inactivation of the retinoblastoma (pRb) and p53 tumor suppressor proteins, we addressed the role of p53 in the development of retinoblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
201
4

Year Published

1995
1995
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(215 citation statements)
references
References 56 publications
10
201
4
Order By: Relevance
“…Lens cells in transgenic mice with lens-speci®c de®ciency in RB function are found to undergo apoptosis. When both RB and p53 functions are inactivated in lens cells, apoptosis is inhibited and lens tumours are developed (Pan and Griep, 1994;Howes et al, 1994;Morgenbesser et al, 1994).…”
Section: P19arf Links the Tumour Suppressors Rb And P53mentioning
confidence: 99%
“…Lens cells in transgenic mice with lens-speci®c de®ciency in RB function are found to undergo apoptosis. When both RB and p53 functions are inactivated in lens cells, apoptosis is inhibited and lens tumours are developed (Pan and Griep, 1994;Howes et al, 1994;Morgenbesser et al, 1994).…”
Section: P19arf Links the Tumour Suppressors Rb And P53mentioning
confidence: 99%
“…Although such a possibility can not be excluded for Rb, it was recently reported that ectopic expression of DRb is not su cient to induce apoptosis (Janicke et al, 1996;Tan et al, 1997). There is strong evidence that Rb can exert a potent antiapoptotic activity: Rb-de®cient cells are more sensitive to apoptosis than cells expressing Rb (Berry et al, 1996;Clarke et al, 1992;Fan et al, 1996;Jacks et al, 1992;Lee et al, 1992), and the production of viral oncoproteins such as E1A and E7, which inhibit Rb by binding to the B pocket, enhances susceptibility to apoptosis (Howes et al, 1994;Rao et al, 1992). In addition to Rb cleavage, TGFb-mediated apoptosis was always associated with a large decrease of total Rb expression consistent with Rb having a protective e ect ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…In vivoexperimental support for this concept has been published scarcely. In one study, disruption of pRb function in retinal cells of transgenic mice was leading to tumor formation only in the absence of wildtype p53 function, which otherwise induced apoptosis of the retinal cells (Howes et al, 1994). In a recent study, the expression of Bcl-x L in pancreatic b-cells of transgenic mice accelerated tumor development induced by SV40 large T antigen (Naik et al, 1996).…”
Section: Cooperation Between C-myc and Bcl-2 During Mammary Carcinogementioning
confidence: 99%